2017
DOI: 10.2741/4471
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation of autophagy in cardiovascular disease

Abstract: Autophagy, a form of lysosomal degradation capable of eliminating dysfunctional proteins and organelles, is a cellular process associated with homeostasis. Autophagy functions in cell survival by breaking down proteins and organelles and recycling them to meet metabolic demands. However, aberrant up regulation of autophagy can function as an alternative to apoptosis. The duality of autophagy, and its regulation over cell survival/death, intimately links it with human disease. Non-coding RNAs regulate mRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 133 publications
(185 reference statements)
0
9
0
Order By: Relevance
“…FOXO3a, a pro-autophagitic factor, is negatively regulated by both miR-212 and miR-132. Over expression of miR-212 and miR-132 significantly disturbs autophagy and results in drastic cardiac hypertrophy and heart failure [ 69 , 89 ]. Additionally, the energy sensing pathway of AMPK can be blocked by disruption of the α1 subunit (AMPKα1), and activation of miR-148b directly inhibits its expression [ 90 ], thereby blocking the entire AMPK assembly.…”
Section: Mirnas In Cardiovascular Diseasesmentioning
confidence: 99%
“…FOXO3a, a pro-autophagitic factor, is negatively regulated by both miR-212 and miR-132. Over expression of miR-212 and miR-132 significantly disturbs autophagy and results in drastic cardiac hypertrophy and heart failure [ 69 , 89 ]. Additionally, the energy sensing pathway of AMPK can be blocked by disruption of the α1 subunit (AMPKα1), and activation of miR-148b directly inhibits its expression [ 90 ], thereby blocking the entire AMPK assembly.…”
Section: Mirnas In Cardiovascular Diseasesmentioning
confidence: 99%
“…Macroautophagy involves the formation of double-membrane-bound vesicles called autophagosomes that engulf cytoplasmic proteins and organelles; these autophagosomes are trafficked to lysosomes for degradation 24,25 . The physiological significance of miRNA-autophagy interconnection in human diseases such as cancer and cardiovascular diseases has been documented in recent years 26,27 . The first link established between miRNAs and autophagy showed that miR-30a directly targets Beclin-1 resulting in decreased autophagic activity in cancer cells 28 .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs participate in multiple biological processes, including autophagy [79-81]. Recent studies have shown that miR-423-5p is upregulated in serum of HCC patients treated with sorafenib and higher expression of secretory miR-423-5p is correlated with an improved prognosis.…”
Section: Autophagy and Cancermentioning
confidence: 99%